The attack of Etiela zinckenella Treitschke on soybean varieties - Sempurna Ginting; Hesti Pujiwati; Usman Kris Djoko; Bambang Gongo Murcitro; Edi Susilo (Universitas Lampung, 2022)
The attack of Etiella zinckenella Treitschke on soybean varieties. Soybean is an important food and source of vegetable protein. One of the problems in soybean cultivation in Indonesia is the presence of pests. Integrated pest control (IPM) techniques are increasing along with the awareness of the importance of environmentally friendly sustainable agriculture. One component of IPM is the use of pest-resistant varieties. This study aimed to examine the effect of the soybean varieties against E. zinckenella Treitschke. This research was conducted with a factorial Randomized Completely Block Design (RCBD). The first factor was the type of organic fertilizer with a dose of 10 tons/ha: (P0= control, P1= Bokashi, P2= Vermikompos, P3=cow manure). The second factor is soybean varieties, which were: V1= Dena 2, V2= Dering 1, V3= Deja 2, V4= Deja 1, V5= Devon 1, V6= Devon 2, V7= Derap 1, V8= Derap 2, V9= Devatra 1, V10 = Devatra 2, V11= Detam 1, V12= Detam 2. The results showed that the interaction between varieties and organic fertilizer significantly affected the percentage of pod borer attack. The interaction between P1 x V8 varieties and between P2 x V6 varieties resulted in the highest percentage of pod borer attack and it was significantly different from other interactions, but not significantly different from P3 x V9, P3 x V5, P2 x V11, P1 x V6, P0 x V11, and P0 x V6.